The Relation Between Diet, Plasma Cholesterol and Atherosclerosis in Pigeons, Quails and Chickens - Bavelaar, F.J.; Beynen, A.C. (International Journal of Poultry Science, 2004)
A literature survey was conducted to determine the relationship between plasma cholesterol concentrations and the severity of diet-induced atherosclerosis in pigeons, quails and chickens. A direct relationship was found between plasma cholesterol and atherosclerosis as induced by cholesterol feeding. In general, dietary polyunsaturated fatty acids versus saturated fatty acids lowered plasma cholesterol concentrations in the three avian species